Application of Qual2Kw model as a tool for water quality management: Cértima River as a case study - Oliveira, B. (2019)
Modelling can be a useful management tool because models allow the understanding of water body response to different pollution pressure scenarios which may help on the decision-making process and in prosecuting the Water Framework Directive objectives. This study aims to evaluate the usage of simple water quality models (Qual2Kw) applied to small river basins in order to better understand the response of a river to different loads of nitrogen and phosphorus. Qual2Kw model was applied to Cértima River (Portugal), a small river that ends in a shallow lake called Pateira Fermentelos and represents a very important ecosystem to the local community. Along its pathway, Cértima River has a significant enrichment in nutrients due to agriculture, livestock, domestic sewage and industrial effluents discharged into the river. In case of nitrogen, the highest loads are from domestic (44%) and diffuse (35%) sources. The main sources of phosphorous are domestic (46%), livestock (24%) and diffuse sources (20%). Cértima River is strongly enriched with nutrients, and neither nitrogen nor phosphorous is limiting the algal growth. According to the criterion of Dodds et al. (Water Res, 32(5):1455-1462, 1998), the river is classified as eutrophic. By comparing in stream measurements with Qual2Kw simulations, it can be concluded that it would be necessary to decrease the actual pollutants loads of nitrogen and phosphorous 5 and 10 times, respectively, in order to change Cértima River classification from eutrophic to mesotrophic.